1990
DOI: 10.1136/gut.31.8.896
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rectal sensitivity after hypnotherapy in patients with irritable bowel syndrome.

Abstract: It has been claimed that hypnotherapy may influence a number of physiological parameters not readily amenable to conscious control,"4 and it is therefore possible that its effect in the irritable bowel syndrome results from a direct action on the gut. On the other hand, it is known that patients with the irritable bowel syndrome have a high incidence of psychopathology'5"6 and it may be that improvement during hypnotherapy is secondary to its psychotherapeutic potential.It was the purpose of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 18 publications
2
86
0
4
Order By: Relevance
“…The reason for this choice was to avoid a carry-over effect, in view of the reported long-lasting effect of hypnotherapy on rectal sensitivity in functional bowel disorders. 23 We acknowledge the potential bias, as training in a medical procedure may decrease the procedure-related stress. However, we were unable to detect any influence of desensitization and/or different posture by repeatedly testing the HSs in a semirecumbent position while listening to relaxing music, compared with the basal test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this choice was to avoid a carry-over effect, in view of the reported long-lasting effect of hypnotherapy on rectal sensitivity in functional bowel disorders. 23 We acknowledge the potential bias, as training in a medical procedure may decrease the procedure-related stress. However, we were unable to detect any influence of desensitization and/or different posture by repeatedly testing the HSs in a semirecumbent position while listening to relaxing music, compared with the basal test results.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 It has been shown that hypnosis can be used to modulate gastric secretion, 21 but no data are available on its potential effect on gastric motor function. 22,23 We postulate a gastroprokinetic influence of hypnosis that may be beneficial in functional dyspepsia. Accordingly, the aim of the present study was to assess the effect of a single hypnosis session on gastric emptying in healthy subjects (HS) and in dyspeptic patients and to compare it with that of oral cisapride in a standard therapeutic regimen.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that although anxiety declined during HT, there was no correlation with symptom improvement (r ϭ 0.220, P ϭ 0.185), suggesting that the beneficial effect cannot be attributed to anxiety reduction alone. The observation that HT can influence gastrointestinal physiologic function 17,18 might suggest that the improvement observed in FD may result from some modification of gastric motility, gastric accommodation, or visceral sensitivity. It is of interest that although HT has been shown to modify gastric acid secretion, 15 its effects on other parameters of gastric physiology have not yet been assessed, although studies of this nature are now underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 HT has also been demonstrated to have the capacity to normalize visceral sensitivity and modulate motility in the gastrointestinal system. 17,18 The aim of this study was to assess the efficacy of HT compared with supportive therapy coupled with placebo medication or with medical management in the shortand long-term treatment of FD. Particular attention was given to controlling for time spent with patients.…”
Section: Background and Aimsmentioning
confidence: 99%
“…27 36 Several studies have examined the effects that hypnotherapy treatment may have on the experience of experimental visceral stimuli and other physiological factors. [37][38][39][40] Despite the fact that hypnotherapy has been used to treat IBS successfully for more than 20 years, the neural mechanisms of pain relief after a course of hypnotherapy still remain unclear. There is evidence, however, that hypnosis, for example, exerts its effect on the pain-processing regions of the central nervous system.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%